Modeling of Three-Dimensional Hierarchical Porous Materials Organized by Means of Nanosphere Self-Assembly - I. E. Kononova; V. A. Moshnikov; P. V. Kononov (Известия высших учебных заведений России: Радиоэлектроника, 2017)
The article considers possibilities of using modeling fo r the development of two promising areas of modern nanomaterials, i. e.  materials with a hierarchy of pores organized hierarchical self- assembly and hierarchical structures with nanoporous elements. The  pore size of hierarchical structures was estimated by means of quasi- two-dimensional projection of three-dimensional deterministic fractal Julien aggregate. Three-dimensional modeling of hierarchical  structures organized by means of nanosphere self-assembly was conducted in the Autodesk 3ds Max environment. The article provides analysis of dependences of porosity, density, specific  surface area of fractal structures on the size of aggregates (with the  appearance of new pore levels of hierarchical materials),  dependences of the porosity change in the case of replacement of primary identical spherical particles on porous spheres.